Padaleman Karuhun Sebagai Konsep Spasial Permukiman Kampung Adat Kuta Kabupaten Ciamis - 20070323301, Sugih Dinul Yakin (Bandung Conference Series: Urban & Regional Planning, 2025)
Abstract. This study examines the spatial social consciousness of the community of Kampung Adat Kuta, Ciamis Regency, in symbolically and morally interpreting their living space. This village represents one of the Sundanese indigenous communities that continues to preserve its ancestral social structures and values across generations, including the practices of pamali (taboos), the conservation of Leuweung Gede (sacred forest), and rituals such as Babarit and Teya. The research aims to understand how social and spatial realms are constructed based on ancestral awareness (Inget Karuhun), and how these values are embodied in spatial arrangements through the concept of Padaleman Karuhun. The study employs Alfred Schutz’s framework of social phenomenology, emphasizing the concepts of Lifeworld (Lebenswelt), intersubjectivity, and social typification. A qualitative-descriptive method is used, with data collected through participatory observation, in-depth interviews with customary leaders and residents, and documentation of cultural artifacts. The findings reveal that ancestral consciousness shapes the structure of social actions and spatial organization in everyday life. The concept of Inget Karuhun is not merely a historical recollection but serves as a moral foundation continually reproduced through rituals, taboos (pamali), and sacred spatial structures such as Padaleman Karuhun. By applying Schutz’s framework of Vorwelt, Umwelt, Mitwelt, and Folgewelt, this study maps how spatial experiences are intergenerational and infused with ecological ethics. In conclusion, Kampung Adat Kuta exemplifies an indigenous spatial system sustained not only physically but also as a living moral and cosmological order. This research contributes to the discourse on value-based and phenomenological approaches to spatial planning, while offering a critique of modern planning paradigms that tend to be technocratic and ahistorical.